The process behind product development and marketing. Founding Arctic Barley - Hildur Guðrún Baldursdóttir 1991- (2018)
The main ingredient in Arctic Barley products is Icelandic popped barley. By popping barley, it gives the grain an interesting crunchy texture without the adding or removing any properties and transforms the grain into a new, exciting and fresh ingredient. Barley is the most cultivated grain harvested in Iceland, however it is mostly used for animal feed. Barley is a nutritious grain and consumption is considered to have health benefits and research has shown that the fibre content in barley can lower the risk for heart disease and diabetes. This project reviews many of the necessary approaches needed when introducing a new product to the market. The goal of this thesis was to go through all processes needed when making successful business model and preparing the product Arctic Barley for the market. Quality control is discussed and necessary measurements in relation to shelf life are performed where water activity and microbiological properties were measured. A sensory evaluation was performed and Q10 was calculated from the results. Consumer surveys were conducted and their results were used in the market analysis of Arctic Barley. Arctic Barley’s value proposition was found by using a positioning statement and a SWOT analysis was conducted. Market size and target consumers and customers were evaluated along with the estimated cost analysis for production of Arctic Barley products. The results show that popped barley is a safe and stable product but could be sensitive to rancidity due to low water activity. Arctic Barley has received much interest from consumers and larger companies which indicates that there is a market for Arctic Barley. Aðalinnihaldsefni Arctic Barley er Íslenskt poppað bygg. Með poppun fær byggið skemmtilega stökka áferð og er engu bætt við eða tekið frá korninu sem umbreytir því í hráefni sem er nýtt, spennandi og ferskt. Bygg er sú korntegund sem mest er ræktuð á norðlægum slóðum en þrátt fyrir það er lang stærstur hluti þess byggs sem ræktað er nýtt í skepnufóður. Bygg er ...